"None so queer as folk": Gendered expectations and transgressive bodies in leadership. (August 2013) - Muhr, Sara L; Sullivan, Katie Rose
This paper investigates the relationship between the body and leadership through a case study of a transgender leader. The study shows that the leader's body, presumed gender, and gendered appearance are salient markers that employees use to make sense of leaders and leadership, and that this gendered nature of leadership shows the deep roots of gender dichotomies and the heterosexual matrix that permeate our understanding of leadership. These two findings lead us to emphasize the need to queer leadership. All leaders experience gendered restrictions, to some extent, via the social norms and expectations of the way leadership should be performed. The construction of leadership through a transgender body reminds us to stay open to the exploration of performativity, particularly the relationships between bodies, gender, sexuality, and leadership and how any body can benefit from queering leadership.